Leukocyte traffic control: a novel therapeutic strategy for inflammatory bowel disease – an update. (April 2013) - Cesarini, Monica; Fiorino, Gionata
Adhesion molecules play a key role in the pathogenetic mechanisms of inflammatory bowel disease (IBD), both in Crohn's disease (CD) and ulcerative colitis (UC). In the last decade, some progress has been made in understanding their key role in leukocyte trafficking control in terms of basic research, but evidence of clinical efficacy is lacking. In the last 2 years, new molecules directed against integrins and integrin receptors have been developed and investigated in clinical trials, showing that anti-α4β7 integrin agents can be effective and safe for the induction and maintenance of remission in active CD and UC. Preliminary data show that anti-MAdCAM, anti-β7 and anti-integrin receptor agents are not all effective in IBD. Such results open new perspectives on clinical management of IBD, and new directions in understanding the role of adhesion molecules and leukocyte recruitment both in CD and UC.